Reducing Overtreatment in Gynecologic Oncology: The Case for Less in Endometrial and Ovarian Cancer - Temkin, Sarah M.; Tanner, Edward J.; Dewdney, Summer B.; Minasian, Lori M. (Frontiers in Oncology, 2016)
A growing awareness of the harms of overtreatment in cancer care has reached physicians, patients, health policy makers and medical researchers. Overtreatment exposes patients to the risk of adverse events from procedures or medications that were not necessary. This review examines common practices in gynecologic malignancies which are unlikely to produce direct benefit to patients with these malignancies, but are likely to produce harms. Specifically, we will explore the utility of lymphadenectomy and adjuvant radiation for women with early staged endometrial cancer; and screening for recurrence and continuous chemotherapy for advanced stage ovarian cancer patients.